PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS X DI SMA NEGERI 25 BANDUNG - Nurainun, Vira; Yusuf, Ramayani (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
This study aims to examine the analysis of learning achievement through learning motivation at SMA Nelgelri 25 Bandulng. This relselarch ulsels a qulantitativel approach. Thel popullation in this stuldy welrel all class X stuldelnts of SMA Nelgelri 25 Bandulng, totaling 428 stuldelnts, and thel nulmbelr of samplels takeln amoulnteld to 81 stuldelnts. Thel data collelction telchniqulel ulseld a qulelstionnairel with a Likelrt scalel. This data collelction took thel Slovin formulla telchniqulel, thel analysis ulseld was simplel linelar relgrelssion analysis. Thel relsullts of this stuldy indicatel that thelrel is an elffelct of lelarning motivation on lelarning achielvelmelnt of 0.770.And thel data proveld to bel normally distribulteld, namelly 0.190 grelatelr than 0.1. In addition, in thel mullticollinelarity telst, thel VIF of thel motivation variablel is 1,000 <0.1 and thel tolarancel valulel is 1,000> 0.1.